Dileme pri obravnavi starostnika v ambulanti družinske medicine - Lokar, Rok (Zdravniški vestnik, 2008)
Treating elderly patients yields numerous dilemmas, both medical and non-medical. Decision-making and treatment are further complicated by the lackof guidelines and recommendations, which lays the choice of action upon the individual physician. This makes the assurance of quality and consistency of treatment impossible. Besides, the clinical guidelines are not suitable forgeneral practice work. To provide quality care for the elderly in general practice, we need proper recommendations and guidelines that need to be developed in the primary health care setting. Social dilemmas present themselves as a particular difficulty due to inaccessibility of the proper social services and institutions.
Keywords: Aged; Družinska medicina; Family Practice; Starostniki